Gaspipe confessions of a Mafia boss - Carlo, Philip (William Morrow, 2008)
Anthony "Gaspipe" Casso is currently serving thirteen consecutive life sentences plus 455 years at a federal prison in Colorado. Now, for the first time, the head of a mob family has granted total access to a journalist--the most intimate, personal look into the world of La Cosa Nostra ever seen. Born into a Mafia family, Casso early proved his talent for "earning"--concocting ingenious schemes to hijack trucks, rob banks, and import vast quantities of drugs. He also had an uncanny ability to work with the other families, and forged strong ties with the Russian mob. By the time Casso took the reins of the Lucchese family, he was a seasoned boss, a very dangerous man. But when the law finally caught up with him in 1994, rather than stoically face the music, Casso turned state's evidence and helped put an end to an era.--From publisher description.